Descriptive Analysis of The Obligation To Support and Assist Palestine in The Defense Economy for Muslim - Aditya Rahman; Zainal Abidin; Sri Sundari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research explores the importance of the task of supporting and assisting Palestine in the field of economic defense for Muslims. This research aims to highlight the importance of helping our brothers and sisters in Palestine and fulfilling our obligations to Allah. Through descriptive analysis depicting obligations and responsibilities towards Palestine, this research seeks to provide insight into the moral and ethical dimensions of supporting a just cause. By examining the principles of cooperation in goodness and benevolence as outlined in Islamic teachings, this research underlines the importance of solidarity with those in need. The findings of this research underscore the important role that individuals and society play in upholding justice and compassion in the face of adversity. Ultimately, this study serves as a call to action for all believers to actively engage in efforts to support and assist Palestine in their economic defense.